Analisis Kuat Tekan Dan Permeabilitas Beton Dengan Agregat Halus Campuran Pasir Merah Purwodadi Dan Pasir Kaliworo Klaten - Prasetya, Rizal Yoga; , Basuki, S.T, M.T (2017)
Concrete is a composite material consist of coarse and fine aggregate mixed with water and cement as a binder and a filler between coarse and fine aggregate. The wider usage of concrete building structures will effect to increasing of materials such as sand, gravel, and cement. Fine aggregate or popularly called sand is the most widely material used in the construction industry, so the needs of the sand will be more and more every day especially in the city area that has very rapid development. As an alternative for the supply of sand, there is another sand that has not been used for concrete mixes called red sand from Grobogan. In this experiment, the red sand used as aggregate to make concrete mixture with Kaliworo Klaten sand in order to find the maximum value of compressive strength and permeability in the concrete mix. This research used experimental method with a cylinder sample in diameter of 15 cm and 30 cm high for compressive strength test and a diameter of 7.5 cm, height 15 cm for permeability testing. Planning of concrete in this research using method SNI. T-15-1990-03 compressive strength required within 28 days is 20 MPaf'c, cement water factor of 0.5. This study uses a mixture of red sand as much as 0%, 10%, 30%, 50%, 70%, 90%, 100%. The results of this experiment, the compressive strength values obtained average of 21.95 MPa. 21.61 MPa. 21.05 MPa. 20.82 MPa. 24.22 MPa. 20.37 MPa. 20.03 MPa. With an average from maximum yield compressive strength obtained is 24.22 MPa with a mixture of 70% sand and 30% Kaliworo red sand. While the influence of a mixture of red sand and Kaliworo sand to permeability coefficient values with a mixture of red sand as much as 0%, 10%, 30%, 50%, 70%, 90%, 100% permeability coefficient values is 3,8132 x 10-7m / dt, 4,14815 x 10-7 m / sec, 5,24507 x 10-7m / sec, 4,4563 x 10-7m / sec, 3,60563 x 10-7m / sec, 4,18301 x 10-7 m / sec, 4,07303 x 10-7 m / sec.